Leu-M1--a marker for Reed-Sternberg cells in Hodgkin's disease. An immunoperoxidase study of paraffin-embedded tissues. - Pinkus, G. S. (1985)
Monoclonal antibody to Leu-M1, a granulocyte-related differentiation antigen, represents a highly effective reagent for detection of diagnostic Reed-Sternberg (R-S) cells and variants in paraffin-embedded tissues of Hodgkin's disease. In 69 of 73 cases of Hodgkin's disease (41 nodular sclerosis, 25 mixed cellularity, 4 lymphocyte predominance, and 3 lymphocyte depletion types), R-S cells were strongly immunoreactive for Leu-M1. Four cases of lymphocyte predominance Hodgkin's disease (nodular) were uniformly nonreactive for Leu-M1. In most of the positive cases (57/69, 83%), the majority (60-90%) of R-S cells and variants exhibited immunoreactivity for Leu-M1. A characteristic staining pattern included granular and/or vesicular cytoplasmic immunoreactivity, often with a prominent globular paranuclear reaction product, and membrane staining with highly irregular cytoplasmic borders. Evaluation of B-cell (37 specimens), T-cell (20 specimens), and true histiocytic (3 specimens) neoplasms and a case of mastocytosis revealed immunoreactivity for Leu-M1 only in 1 B-cell and 4 T-cell malignancies. The staining patterns in these cases, however, clearly differed from that observed for R-S cells. Studies of nonneoplastic lymphoid tissues (38 total) demonstrated that lymphoid cells were typically nonreactive; histiocytes revealed variable reactivity for Leu-M1. Occasional histiocytes of the sinusoidal network of lymph nodes, particularly in toxoplasmic lymphadenitis, exhibited a staining pattern (membranous/cytoplasmic/paranuclear) similar to that observed for R-S cells. Leu-M1 represents a potentially helpful diagnostic discriminant in the assessment of Hodgkin's disease and its distinction from non-Hodgkin's lymphomas and other lymphoid proliferations.